Social studies excursions, K-3. Book two, Powerful units on communication, transportation, and family living - Alleman, Janet; Brophy, Jere E.; Knighton, Barbara (Portsmouth, NH : Heinemann, 2002)
A guide to creating educational units on communication, transportation, and family living for students in grades K through three.
Includes bibliographical references.
Reference and Research Book News.
Professional
Keywords: Social sciences -- Study and teaching (Primary); Social sciences -- Study and teaching